THE HISTORY OF THE BUGIS LONTARA CALENDAR OF SOUTH SULAWESI - Perdi Lesmana (Fakultas Syari'ah dan Hukum UIN Walisongo, 2023)
Basically a calendar or calendar is the accumulation and distribution of time with certain time units based on certain events that are used by people around the world to be used as a benchmark and guide or marker of time in their life journey. The Bugis calendar is a calendar that belongs to the Bugis tribe in South Sulawesi and is a cultural heritage that has been passed down from generation to generation and is also a unique calendar because this calendar existed before Islam entered the South Sulawesi region. The purpose of this study is to add to and expand the kazana on the study of astronomy, especially the Bugis people of South Sulawesi and it is hoped that it will also be able to become a reference for information regarding the Lontara Bugis calendar so that this study uses a literature research method that describes systematically, normatively and accurately the objects studied. become the main problem. Currently, the use of the Lontara Bugis calendar has adopted the Hijri calendar, but does not necessarily leave the culture or beliefs of our ancestors regarding the Lontara Bugis calendar.